The Influence of Project Based Learning (PJBL) Learning Model on Spatial Thinking Ability in Class X Geography Learning Eyes in SMA PGRI 2 Palembang - Putri, Ramayana Dwi (Universitas Veteran Bangun Nusantara, 2020)
One of the goals of learning geography is to give students the ability to think spatially. But based on observations in the field, it shows that students' spatial thinking skills have not shown maximum results. This study aims to determine the effect of the Project Based Learning (PJBL) learning model on spatial thinking skills in class X geography subjects at SMA PGRI 2 Palembang. To determine the effect of Project Based Learning (PJBL) on spatial thinking skills, the researcher used the Experimental method. Based on the results of data analysis and discussion on the effect of Project Based Learning (PJBL) learning models on spatial thinking skills in class X geography subjects at SMA PGRI 2 Palembang, it can be concluded that the results of the average data analysis results of the students' experimental class spatial thinking test 76.02 while the control class averages 61.72. Based on the results of the t-test obtained thitung = 8.43 then compared with ttable = 1.66, then tcount> ttable is 8.43> 1.66. These results prove that there is a significant influence between the Project Based Learning (PJBL) learning model on spatial thinking skills in class X geography subjects at SMA PGRI 2 Palembang.